2003
DOI: 10.1111/j.1360-0443.2004.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief interventions for hazardous drinkers delivered in primary care are equally effective in men and women

Abstract: Our results support the equality of outcomes among men and women achieved by brief interventions for hazardous alcohol consumption in primary care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 24 publications
3
60
1
2
Order By: Relevance
“…3 In this way, both genders manifest the same expectations for improvement and must be targeted for intervention. 27 Our findings agree with previous studies that show that alcohol use is associated with other forms of drug abuse. 28 The relationship between cigarette smoking and alcohol use is well documented.…”
Section: Signor Et Alsupporting
confidence: 93%
“…3 In this way, both genders manifest the same expectations for improvement and must be targeted for intervention. 27 Our findings agree with previous studies that show that alcohol use is associated with other forms of drug abuse. 28 The relationship between cigarette smoking and alcohol use is well documented.…”
Section: Signor Et Alsupporting
confidence: 93%
“…While concerns have been raised about the effectiveness of substance abuse treatment for women (Ferrence et al, 1994;Floyd et al, 1996;Hodgins et al, 1997;Schmidt and Weisner, 1995;Schober and Annis, 1996), many studies have found few or no gender differences in treatment outcome across various populations (e.g., Acharyya and Zhang, 2003;Alterman et al, 2000;Ballesteros et al, 2004;Benishek et al, 1992;Foster et al, 2000;Green et al, 2004;Greenfield et al, 1998;Hser et al, 2003;Jerrell and Ridgely, 1995;Marsh et al, 2004;McCance et al, 1999;McLellan et al, 1994;Rohsenow et al, 2000;Sterling et al, 2004;Toneatto et al, 1992;Wong et al, 2002). For example, one recent report (Acharyya and Zhang, 2003) found treatment-related improvements, but only minimal differences in outcomes between men and women in four substance abuse treatment modalities (methadone, non-methadone outpatient, short-term inpatient, and longterm residential).…”
Section: Substance Abuse Outcomes Versus Predictors Of Outcomesmentioning
confidence: 99%
“…However, gender did not predict 12-week outcome measures, including relapse. A recent meta-analysis of seven studies of brief interventions for hazardous alcohol consumption delivered in primary care outpatient settings demonstrated no gender difference in improved treatment outcomes (Ballesteros et al, 2004). A secondary analysis of data from the prospective U.S. National Treatment Improvement Evaluation Study including 1,123 women and 2,019 men in 59 treatment facilities (Marsh et al, 2004) found that receipt of comprehensive services, including educational, housing, and income support, were related to post-treatment outcomes for both men and women.…”
Section: Substance Abuse Outcomes Versus Predictors Of Outcomesmentioning
confidence: 99%
“…The authors noted that the benefits for women receiving brief intervention for problem drinking were not consistent across the studies reviewed. Other reviews with meta-analyses have found brief interventions effective across gender for heavy drinking and hazardous drinking [Wilk et al, 1997;Ballesteros et al, 2004], and extended brief interventions effective in women but not men [Poikolanen, 1999].…”
Section: Efficacy Of Brief Interventions For Reducing Problem Drinkinmentioning
confidence: 99%
“…As the Task Force reviewed the evidence, the science to date pointed to brief alcohol intervention as an effective approach to reducing alcohol use and AEPs. As previously outlined, research indicates that alcohol screening and brief interventions have been found to be effective in multiple settings, including primary care [Bien et al, 1993;Wilk et al, 1997;Poikolanen, 1999;Ballesteros et al, 2004;Whitlock et al, 2004], emergency room [D'Onofrio andDegutis, 2002], community [O'Connor andWhaley, 2007], and college settings [Larimer and Cronce, 2002]. The Task Force recommended promoting the use of evidencebased strategies in these types of settings for women of childbearing age at risk for an AEP.…”
Section: Selective and Indicated Prevention Strategiesmentioning
confidence: 99%